Antihyperlipidemic effect of Punica granatum mesocarp extract (PGME) in rats - Afify, Afaf; Hassan, Zeinab; Abd El-Mageed, Nehal; El-Mahmoudy, Abubakr (International Journal of Pharmacology and Toxicology, 2022)
Hyperlipidemia is an umbrella term that refers to any disorder of elevated level of lipids circulating in the blood; and is considered the most significant risk factor contributing to the prevalence of cardiovascular, hepatic, and other diseases. The present study was designed to evaluate the possible antihyperlipidemic potential Punica granatum mesocarp extract (PGME) in albino rats using high-fat diet model of hyperlipidemia. Forty-two albino rats were utilized in this experiment arranged randomly in seven groups, six rats each, of different treatments. Hyperlipidemia model was induced by incorporating coconut oil (1.5% w/w) and cholesterol (1.5 % w/w) in diet supplied to rats, for 6 weeks (+ve control); test group rats received PGME at escalating doses of 100 or 200 mg/kg, orally, daily for 6 weeks with keeping on high-fat diet; standard group rats received Rosuvastatin at dose of 2 mg/kg, orally, daily for 6 weeks along with high-fat diet; further 2 groups of rats received only PGME at the same dose levels with keeping on normal diet; while rats of -ve control group received only the vehicles of the used agents. Blood samples were picked out at the end of the experimental course for different assays. Clinicochemical analyses revealed that PGME exhibited dose-dependent protection against hyperlipidemia indicated by improved biomarkers, including, lipid profile parameters, namely cholesterol, triacylglycerols and lipoproteins; enzymatic hepatic parameters, namely, AST, ALT, and GGT; and non-enzymatic parameters, namely, total protein, albumin, globulins, total bilirubin, conjugated bilirubin, unconjugated bilirubin. The mechanism of the obtained lipid profile improvement of PGME may be based on the phytochemical principals Tannins, Phenolics and Flavonoids, indicated by preliminary detection tests. Data of the present study may suggest PGME as a good natural source for promising antihyperlipidemic remedies.Â Â